Menelisik Respon Pemerintah Daerah Kabupaten Sumbawa Barat dalam Memfasilitasi Proses Pembebasan Lahan Pembangunan Smelter - Purwadinata, Subhan; Ferdaus, Nadia Nuril (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The purpose of this Community Service Activity is to examine the response of the community and government regarding the smelter development program. This activity was conducted in the villages of Benete and Maluk, West Sumbawa Regency. The activity, held in December 2021, involved 126 participants. The details of the participants include 6 local government officials, 15 youth representatives, 15 community leaders, 15 religious leaders, and 15 community members directly impacted by the Smelter project in Maluk village, as well as 15 youth representatives, 15 community leaders, 15 religious leaders, and 15 community leaders directly impacted by the Smelter project in Benete village. The method used in this activity is the interview method with informants through a qualitative approach. The research findings indicate that the local government supports the construction of a smelter in Sumbawa Regency to boost development and improve the local economy, strongly backing the smelter project in West Sumbawa Regency by facilitating land acquisition.